PENGARUH AUDIT TENURE DAN INDEPENDENSI AKUNTAN PUBLIK TERHADAP KUALITAS AUDIT DAN IMPLIKASINYA TERHADAP KEPUASAN AUDITEE (Survei Pada Kantor Akuntan Publik Yang Terdaftar Di Bapepam-LK) - Eva Marin Sambo (Indonesian Journal of Economics and Business, 2012)
Financial scandals and cases of violations that occurred in recent years has become the world's attention which raises the question of whether the audit firm has provided audit services that have a high quality audit,  thus has caused the decline of public confidence in audit quality produced by a public accountant, which resulted in questionable integrity and objectivity of public accountant as a party that audited the financial statements of the company. To improve audit quality, length of engagement with the client's KAP and independence of public accountants may be a factor to be considered, which in turn will also increase the satisfaction of auditees.This study examined the influence of audit tenure and public accountants independence to audit quality and their implication to auditee satisfaction. In this study, research method used is a method verifikative. Respondents are partners and managers in the KAP registered with Bapepam-LK and manager of finance/accounting and internal audit listed on the Indonesia Stock Exchange in 2011. The sampling technique using a purposive sampling. The data was collected through questionnaires. Analysis of data for testing hypotheses using Path Analysis.These results of this study that show: (1) the audit partner tenure, especially the length of an audit of the audit client is an important factor associated with the public accountants independency, (2) the high audit quality is influenced by high public accountant independency, but public accountant independency would be affected/decrease if the audit tenure is long, (3) The high audit quality will be increase auditee satisfaction, however the high audit quality will also be affected by the audit tenure, where if audit tenure is long, the audit quality will decrease, resulting in auditee satisfaction also declined.